Pengaruh Motivasi, Kepuasan Kerja Dan Disiplin Kerja Terhadap Kinerja Anggota Kepolisian Pada Satuan DITSAMAPTA POLDA NTB - Sofia Maudilia Juniarti; Sri Wahyulina; Santi Nururly (Universitas Maritim AMNI Semarang, 2023)
This study aims to analyze the effect of motivation, job satisfaction and work discipline on the performance of members of the Ditsamapta Polda NTB. The type of research used is causal associative research. The data analysis technique used was Multiple Linear Regression using the IBM 26 version of SPSS. Respondents in this study were all members of the NTB Ditsamapta Polda, totaling 40 employees. The results of the analysis show that: (1) Motivation has a positive and significant effect on Members of Ditsamapta Polda NTB (2) Job satisfaction has a positive and significant effect on the Performance of Members of Ditsamapta Polda NTB (3) Work Discipline has a positive and significant effect on the Performance of Ditsamapta Polda NTB.the result of this study show that job satisfaction has a dominant influence on the performance of members of Ditsamapta Polda NTB